The defensive playing style was associated with match-running performance and team success in the FIFA Women's 2023 World Cup - Branquinho, L.; de França, E.; Titton, A.; González-Fernández, F. T.; Teixeira, J. E.; Forte, P.; Lopes Verardi, C. E.; Hirota, V. B.; Ferraz, R.; Teoldo, I.; Thomatieli-Santos, R. V. (Frontiers in Sports and Active Living, 2026)
Introduction: